An Adult Patient with Ocular Myasthenia and Unusually Long Spontaneous Remission - Jasem Al-Hashel; Hanaa M. Rashad; Rossen T. Rousseff (Case Reports in Neurological Medicine)
A male patient developed ocular myasthenia gravis (MG) at the age of 33. He was anti-acetylcholine receptor antibody (anti-AChR Ab) negative. He received cholinesterase blocker for 5 months and went into a complete clinical remission that lasted untreated for 17 years. He relapsed recently with ocular symptoms only. He is now anti-AChR Ab positive and SFEMG is abnormal in a facial muscle. The patient is controlled with steroids. He had one of the longest spontaneous remissions reported in the natural history of MG, particularly unusual for an adult with the disease.